Introduction to Apache Spark 2.0 : a primer on Spark 2.0 fundamentals and architecture - Lee, Denny (O'Reilly Media, 2017)
"This video series highlights what's new in Apache 2.0 and reviews its core concepts. The course starts with a high-level overview of Spark's components and then dives into Spark 2.0's three main themes: simplicity, speed, and intelligence. The simplicity section describes how Spark 2.0 unifies the Spark APIs and Spark session, and how Spark 2.0 simplifies machine learning via ML pipelines. The speed section illustrates how Spark 2.0 improves Spark performance with the push toward whole-stage code generation. And the intelligence section provides a quick primer on Spark Streaming and an introduction to the concepts of Structured Streaming. The course is designed for data scientists and data engineers with some basic experience using machine learning tools such as Python scikit-learn."--Resource description page.